Logistics for circular economy : a case of e-scooters in Singapore - Ahmad Afiq Adam (Nanyang Technological University, 2020)
As the popularity of e-scooters continue to soar in Singapore, the lack of a proper disposal management system may raise concerns on the environmental and sustainability practices. With no known system in place to deal with the disposal of these products, we believe that the application of circular economy and reverse logistics will be effective. Our research dives into the study of an effective loop-system in related industries. We will analyse product recovery trends and management systems of several countries and determine its applicability into the Singapore’s e-scooter industry. Although this study is centred around logistical systems, the report will discuss other factors due to the comprehensive and holistic nature of a circular economy. The report will then consolidate the key factors taken from other countries and propose strategies moving forward. All in all, an effective closed-loop system can only be successful if everyone plays their responsible role and this starts with the government.